The design, synthesis and biochemical evaluation of analogues of dehydroepiandrosterone (DHEA) and novel selective oestrogen receptor modulators (SERMs) - Lauhoff, Sandra Michelle (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2002)
This thesis is presented in four sections. In the first section the synthesis of a series of B ring derivatives of dehydroepiandrosterone (DHEA) is described. DHEA is the most abundant steroid in human plasma and has been associated with anti-obesity properties. It is proposed that chemical modification of DHEA allows for the retention of the beneficial anti-obesity properties of DHEA, while preventing its further metabolism to androgenic steroids. In the present work, DHEA was modified at position 6 and 7 of the steroid nucleus to yield 7-oxo, 6-nitro and 6-oxo derivatives. Each of these compounds was further modified at position 3 to yield a series of carboxylic acid and amino acid esters. 7a-Hydroxy and 7p-hydroxy derivatives of DHEA were prepared, and the preparation of 6a-hydroxy and 6p-hydroxy derivatives was also investigated. These compounds were then assayed using an in vitro cell culture assay in rat L6 myoblasts (G8-C5) for their ability to stimulate glucose consumption in cells as a measure of possible anti-obesity activity, using rosiglitazone, a PPARy agonist, as reference compound. Sections two, three and four of the thesis relate to the design, synthesis and biochemical evaluation of novel anti-cancer agents, which are analogues of the breast cancer treatment tamoxifen. Tamoxifen is a selective oestrogen receptor modulator (SERM) with a triarylethylene structure, which has oestrogenic activity in bone and endometrial tissue, yet antagonises the actions of oestrogen in other tissues including breast tissue. In the present work, it was proposed to develop novel triarylethylenes with a preferable, more selective activity profile than that of tamoxifen.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin